Factors affecting mortality in neonatal pneumothorax Mortality in neonatal pneumothorax - Bakal, Unal; Tartar, Tugay; Sarac, Mehmet; Aydin, Mustafa; Genc, Ercan; Kazez, Ahmet (Bayrakol Medical Publisher, 2021)
Aim: We aimed to determine the prevalence, demographic and clinical features of neonatal pneumothorax (NP) and to investigate the effects of these variables on mortality. Material and Methods: The medical records of patients with NP who were treated with tube thoracostomy method between 2004 and 2018 were examined. The causes, clinical features, additional anomalies, demographic data and mortality rate of NP patients were investigated. The results were compared with chi-square, Mann-Whitney U, ROC (receiver operating characteristic) analysis and Binary Logistic Regression test. Results: NP prevalence in our setting was 1.56%. Sixty-six of the patients were girls and 54 were boys. Mortality was significantly higher in female newborns (p = 0.005). mechanical ventilator support (p < 0.005), cardiopulmonary resuscitation history (p = 0.001). birth-weight of < 1380 g (p 0.001) and gestational age of < 30 weeks (p = 0.001) and diagnosis time of > 5 days (p = 0.001). Among congenital heart diseases, mortality was also significantly higher in patients with patent foramen ovale + patent ductus arteriosus and atrial septal defect + patent ductus arteriosus (p - 0.032). In addition, mortality was significantly higher in the patients with respiratory distress syndrome (p = 0.01). However, mode of delivery, pneumothorax side, presence of additional anomalies, Apgarscore, age of diagnosis did not have significant effect on mortality (p > 0.005). Discussion: The neonates with <= 1400 g birth-weight, 33 weeks gestational age, > 5 postnatal days, history of CPR and mechanical ventilator support, and female gender constitute a sensitive population for development of pneumothorax and therefore should be closely monitored.
Keywords: Respiratory Distress Syndrome; Neonate; Pneumothorax; Risk Factor; Mortality